Computer-aided Drug Designing for the Identification of High-Affinity Small Molecule Targeting CD20 for the Clinical Treatment of Chronic Lymphocytic Leukemia (CLL) - Sinha, Kritika; Majhi, Manisha; Thakur, Garima; Patidar, Khushboo; Sweta, Jajoriya; Hussain, Tajamul; Nayarisseri, Anuraj; Singh, Sanjeev K. (Current Topics in Medicinal Chemistry, 2018)
Background: Chronic lymphocytic leukemia (CLL) is a B-lineage lymphoid malignancy of self-reactive cells that are focused to produce polyreactive natural autoantibodies. Its surface protein marker CD20 plays an important role in the humoral immune response targeting which has emerged as an attractive therapeutic option for the treatment of CLL. The present study explains the interaction of the CD20 with its established inhibitors and to discover the compound having high binding affinity against the target protein receptor. Technically, during the development of new compound through docking studies, best drug among all pre-exist drugs got filtered, hence in reference to docked best drug study moved ahead. Methods: The 3D structure of CD20 was built using homology base fold recognition method using Smith waterman’s Local alignment and standalone Delta Blast algorithms. 23 established inhibitors towards CD20 were selected in this present investigation. Among these inhibitors, etoposide (RMSD value -96.6481) showed high binding capacity with the receptor CD20 which was further subjected to virtual screening. The said screening presented 380 possible drugs having structural similarity to etoposide. Results: The docking studies of the screened drugs separated the compound having PubChem CID: 11753896 (RMSD value -98.5416). Toxicity and interaction profile validated this compound for having a better affinity with the target protein. Conclusively, this research study says that according to ADMET profile and BOILED-Egg plot, the compound (PubChem CID: 11753896) obtained from Virtual Screen could be the best drug in future during the prevention of Chronic Lymphocytic Leukemia. Conclusion: The compound identified in the present investigation can be subjected further for in vitro and in vivo studies for ADMET properties and it could optimize a good profile in the field of pharmacy and bioavailable for suppressing cancer. The pharmacophore study revealed that the drug CID11753896 is a non-inhibitor of CYP450 microsomal enzymes and was found to be non-toxic, similar to the established compound CID36462. It has a lower LD50 value of 2.5423mol/kg as compared to the established compound whose LD50 value is 2.9588mol/kg. Also, the compound was found to be non-carcinogenic.
Keywords: CD20